Rigid Procedure to Calculate the Melting Point of Metal Using the Solid-Liquid Phase (Coexistence) Method - Artoto Arkundato; Wenny Maulina; Lutfi Rohman; Ratna Dewi Syarifah; Mohammad Ali Shafii (Jurnal Ilmu Fisika, 2022)
Melting point, particularly metal, is one of the important data for many applications. For developing new materials, adequate theories for melting point are very crucial. The determination of melting point using the popular phase-change curve method is very easy but usually overestimate. In current work, we determine the melting point of a pure metal (iron) using the method of solid-liquid phase coexistence. For this goal, molecular dynamics simulation was applied to obtain data of trajectories of atoms. Simulation (LAMMPS) and data analysis (OVITO) procedures are strictly applied to obtain the accurate melting point of iron based on the obtained trajectories data. For initial structure design of simulation, we used the ATOMSK program. The melting point of iron obtained using the phase change curve (PCC) method is about 2750 K < TPCC < 3250 K and using the coexistence phase (CP) method is TCP = 2325 K. A more accurate calculation needs to include defects factor in the simulated material and calculation. In this research we use the Morse potential to represent all of the atomic interaction among atoms of Fe material.